Novel Sensor Technology To Assess Independence and Limb-Use Laterality in Cervical Spinal Cord Injury - Brogioli, Michael; Popp, Werner L.; Albisser, Urs; Brust, Anne K.; Frotzler, Angela; Gassert, Roger; Curt, Armin; Starkey, Michelle L. (Journal of neurotrauma, 2016)
After spinal cord injury (SCI), levels of independence are commonly assessed with standardized clinical assessments. However, such tests do not provide information about the actual extent of upper limb activities or the impact on independence of bi- versus unilateral usage throughout daily life following cervical SCI. The objective of this study was to correlate activity intensity and laterality of upper extremity activity measured by body-fixed inertial measurement units (IMUs) with clinical assessment scores of independence. Limb-use intensity and laterality of activities performed by the upper extremities was measured in 12 subjects with cervical SCI using four IMUs (positioned on both wrists, on the chest, and on one wheel of the wheelchair). Algorithms capable of reliably detecting self-propulsion and arm activity in a clinical environment were applied to rate functional outcome levels, and were related to clinical independence measures during inpatient rehabilitation. Measures of intensity of upper extremity activity during self-propulsion positively correlated (p < 0.05, r = 0.643) with independence measures related to mobility. Clinical measures of laterality were positively correlated (p < 0.01, r = 0.900) with laterality as measured by IMUs during "daily life," and increased laterality was negatively correlated (p < 0.01, r = -0.739) with independence. IMU sensor technology is sensitive in assessing and quantifying upper limb-use intensity and laterality in human cervical SCI. Continuous and objective movement data of distinct daily activities (i.e., mobility and day-to-day activities) can be related to levels of independence. Therefore, IMU sensor technology is suitable not only for monitoring activity levels during rehabilitation (including during clinical trials) but could also be used to assess levels of participation after discharge.